Penerapan Teknologi Pralon Biopori Untuk Pengolahan Sampah Organik Pada Kelompok Masyarakat Dasawisma Perak 1 Banguntapan - Febriarto, Prasetyo; Fidali, Nurizka; Nugroho, Hanantyo Sri; Rahmawati, Rahmawati; Rahmawati, Aprilia Putri (Bengawan : Jurnal Pengabdian Masyarakat, 2025)
The purpose of this community service activity is to transfer knowledge of organic waste, through two aspects, namely the social aspect of society regarding awareness in processing waste and there is a production aspect through organic waste processing techniques. This activity is motivated by the problem of partners with the condition of household waste disposal, especially organic waste, then partners do not have the knowledge and skills, and the lack of adequate equipment for waste processing. The method is in the form of training through socialization of the importance of the potential of organic waste to become compost by providing knowledge through material through the display of images and training methods by providing organic waste processing techniques. The results of this community service activity were improved knowledge and skills in organic waste processing using biopore pipe technology. The conclusion of this community service activity was that the application of biopore pipe technology had a positive impact on increasing the capacity of partner groups in managing organic waste, including reducing the waste burden in their respective communities. Training using community-based methods can be an effective strategy for training in the application of biopore pipe technology.